8. Rozwiąż równanie.
b) -3x - 1 + 5x + 7 = 0
c) 4x + 7 - x + 2 = 9


Odpowiedź :

Odpowiedź:

Szczegółowe wyjaśnienie:

-3x - 1 + 5x + 7 = 0

2x+6=0

2x=-6/:2

x= -3

c) 4x + 7 - x + 2 = 9

3x+9=9

3x= 0/:3

x=0

Odpowiedź:

b) - 3x-1 +5x +7=0

   -3x+5x= 1-7

        2x= -6 /:2

        x= -3

spr...   -3*(-3) -1 + 5*(-3)+7= 0

                  9-1 -15 +7=0

                16-16=0

                      0=0

                     L=p

c)   4x+7 -x+2 =9

         4x-x= 9 -2 -7

           3x= 0

             x=0

        spr...   4*0 +7-0 +2=9

                       7+2=9

                          9=9

                         L=P

Szczegółowe wyjaśnienie: